Hubungan Status Gizi dan Tingkat Stres Remaja dengan Kejadian Disminore STIKES Sukma Wijaya Sampang - Fithriani, Zainun Wahida; Fadhila, Fildza (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Menstruation can be an uncomfortable experience, some women have complaints during menstruation. Complaints that arise during menstruation is pain which is known as dysmenorrhea. Based on data from the World Health Organization (WHO) in 2018, it shows that 90% of women experience dysmenorrhea, with 10-15% suffering from severe dysmenorrhea. Indonesia is a country with a high incidence of dysmenorrhea about 55%, especially in women of productive age. One of the determining factors causing dysmenorrhea is nutritional status. Abnormal nutritional status can be a risk of dysmenorrhea. Another factor that can cause dysmenorrhea is stress levels. Dysmenorrhea can be caused by psychological aspects. The research uses a cross sectional approach. The research respondents were 102 Level II students. The sample size was 51 people calculated using the Slovin formula. From the test of the relationship between nutritional status and the incidence of dysmenorrhea, it shows a significance value of 0.000 < α, there is a relationship between nutritional status and the incidence of dysmenorrhea. The results of the test of the relationship between stress levels and the incidence of dysmenorrhea show a significance value of 0.000 < α, there is a relationship between stress levels and the incidence of dysmenorrhea.